What Triggers Inflation in Emerging Market Economics? - Domaç, Ilker; Yücel, Eray M. (World Bank, Washington, D.C., 2013)
Emerging market economies (EMEs) have experienced a noticeable decline in inflation since the mid-1990s. Whether this stable price environment in EMEs is likely to endure and what kind of policies need to be followed to ensure price stability, however, still continue to be questions of considerable policy relevance. The authors investigate the factors associated with the start of 24 inflation episodes in 15 EMEs between 1980 and 2001. They use pooled probit analysis to estimate the contribution of the key factors to inflation starts. Their empirical results suggest that increases in the output gap, agricultural shocks, and expansionary fiscal policy raise the probability of inflation starts in EMEs. Their findings also indicate that a more democratic environment and an increase in capital flows relative to GDP reduce the probability of inflation starts.